PENGARUH CITA RASA, HARGA, STORE ATMOSPHERE, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN - Prawibowo Simbolon; Junita Lubis; Mulkan Ritonga (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the influence of taste, price, store atmosphere, and service quality on consumer satisfaction in Coffee Shops (Warkop). In an era of increasingly fierce business competition, understanding the factors that affect consumer satisfaction is very important for business continuity. The taste of drinks and food, proper pricing, a pleasant store atmosphere, and quality service are key aspects that allegedly affect customer satisfaction. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to consumers of Warkop Gelas Batu 2 Rantauprapat. The sample used was 100 respondents who were calculated using the Wibisono formula, and were randomly selected. Data analysis was carried out using multiple linear regression techniques to test the relationship between free variables (taste, price, store atmosphere, service quality) and bound variables (consumer satisfaction). The results of the study show that all independent variables have a positive and significant influence on consumer satisfaction. Service quality has the strongest influence, followed by price, taste and store atmosphere. These findings indicate that to increase consumer satisfaction, Warkop Gelas Batu 2 must focus on improving service quality, adjusting product prices more competitively, improving product taste quality, and creating a more comfortable store atmosphere. Consumer satisfaction at Warkop Gelas Batu 2 is influenced by several factors that can be managed by business owners. By improving these factors, it is expected to increase customer satisfaction and their loyalty